'It's not all it's cracked up to be': Narratives of promotions in elite professional careers. (September 2020) - Gustafsson, Stefanie; Swart, Juani
How do organizational decision-makers and promotion candidates experience promotions in elite professional careers? Despite literature recognizing that promotions are important career events for organizations and individuals, this question has received little scholarly attention. Drawing on a narrative approach and combining spoken and visual accounts, this article examines how organizational decision-makers and promotion candidates experience the promotion to partnership in law firms. Our study reveals four narratives that illustrate important differences and similarities in their accounts. In the official script, organizational decision-makers uniformly recounted promotions in a detached way, emphasizing objective meanings of career success. In contrast, promotion candidates' accounts were varied, ranging from joy and anticipation in walk in the park, to anger and frustration in dark art to anxiety and ambivalence in bittersweet narratives. The study makes three contributions to the literature on promotions. First, we develop an emotion-based understanding of promotions suggesting that promotions are constructed through people's lived emotional experiences that inform their meaning making of the new role. Second, we argue that promotions are not always positive career events, but potentially contradictory and negative. Third, we contribute to extant research on promotions that has favoured quantitative methodologies by adopting a multimodal approach.